The Covid-19 Pandemic Impact On Learning Students SD Sangubanyu 1 - Fauzi, Kharisma Amar; Fitria, Aura Zayinatul; Priharyani, Ika (Prosiding University Research Colloquium, 2021)
Covid-19 is a major obstacle to Indonesian society especially in the field of education. So governments introduced an online learning system to prevent the spread of the covid-19 virus. But in implementing that system there are still many flaws that are found in particular the role of parents in helping students understand the material presented by their teachers. Parents are engaged to understand the technological development that is a major prerequisite for online study. The purpose of this study is to know how important the role of parents is to the learning result of learners. The study employed a method of observation involving several apprentices from Sangubanyu 1's primary school in the study. The result of the study is that the value of students is consistent with the participation of parents in the work or testing given by their teachers. So it cannot be denied that a student's grades are becoming better than they used to be.